Thermal evolution of the Lesser Himalaya, central Nepal: Insights from white mica compositions and K-Ar ages - Paudel, LP; Itaya, T; Arita, K (Journal of Nepal Geological Society, 2008)
The Lesser Himalayan low- to medium-grade metamorphic rocks in central Nepal are rich in K-white micas occurring as porphyroblasts and matrix defining S1 and S2. Porphyroclasts are usually zoned with celadonite-poor cores and celadoniterich rims. The cores are the relics of igneous or high-grade metamorphic muscovites, and the rims were re-equilibrated or overgrown under lower T metamorphic conditions. The matrix K-white micas defining S1, pre-dating the MCT activity, are generally celadonite-rich. They show heterogeneous compositional zoning with celadonite rich cores and celadonite-poor rims. They were recrystallized at lower T condition prior to the MCT activity. The matrix K-white micas along S2, synchronous to the MCT activity, are relatively celadonite poor and were recrystallized under relatively higher T-condition. Average compositions of recrystallized white micas show northward increase in metamorphic grade conforming inverted metamorphism throughout the Lesser Himalaya. K-Ar dating was performed on different-sized fractions (0.5-1, 1-2, 2-4, 4-6 ìm and #80-100) of nine metapelites samples. The Tansen Group sample is less recrystallized and yields extremely old ages (850-1045 Ma) representing the ages of detrital materials. The Nawakot Complex yields the ages ranging from 458 to 9.5 Ma. Relatively less-sheared and lowergrade (anchizone) samples containing only S1 white micas give the ages of 280-458 Ma, representing the timing of M0 (Pre-Himalayan metamorphism). The youngest age (9.5 Ma) was obtained from the upper part of the MCT zone which experienced intense ductile shearing resulting in S2 and recrystallization (M2) at the temperature of 500-650°C during the MCT activity. Intermediate ages were observed in the epizone to the lower part of the garnet zone where the rocks have two types of white micas defining S1 and S2. The northward younging of white mica ages may have been resulted from the decrease of M0/M2 mica ratio towards the north close to the MCT. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.10